Sustainability of United Nations Recruitment: An Empirical Analysis of Recent Vacancy Advertisements of United Nations Specialized Agencies - Liu, Suyu (European Journal of Sustainable Development, 2020)
This paper examines the sustainability of recruitment in the United Nations (UN), the largest global inter-governmental organization working on sustainable development. It investigates the sustainability of UN recruitment on three main dimensions: remuneration and job stability; meritocracy and fairness; cost and efficiency, with the data from recent vacancy advertisements of two UN specialized agencies. The analytical results suggest that being different from the existing knowledge of UN recruitment, the job stability in UN as shown by the data is higher due to the large proportion of staff vacancies and long-term job contracts. The remunerations to UN job incumbents are high, not only because of the widely-known attractive packages which are provided referring to the highest remuneration levels of national civil service, but also due to the subsidies of working in hardship places. Also, it is found that UN specialized agencies have developed detailed competency frameworks for recruitment to ensure the meritocracy. However, due to the essential monitoring procedures, UN recruitment is often lengthy and costly. Therefore, in the dilemma of meritocracy, fairness, and efficiency in recruitment, efficiency is not highly emphasized in UN recruitment practice, in comparison with meritocracy and fairness. Practical recommendations for improving sustainability of UN recruitment are provided, but more evidence and implications are to be provided by future research. Key Words: United Nations; Recruitment; Sustainability; Meritocracy; Efficiency